Statistics 2 - Dobbs, Steve; Miller, Jane. (Cape Town : Cambridge, 2006)
Statistics 2 corresponds to unit S2. It covers the Poisson distribution, linear combinations of random variables, continuous random variables, sampling and estimation, and hypothesis tests.
Include index.
Keywords: Mathematical statistics -- Problems, exercises, etc; Mathematical statistics. -- Examinations -- Study guides; Mathematical statistics